(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Historical city centers represent the oldest part of the city that reflect its importance and history through a concrete cultural identity with fixed features. These centers maintain their authenticity by maintaining their continuity. However, historical city centers have been exposed to many factors that have affected their structure, especially the physical structure, which required the emergence of a policy to regenerate these vital areas of the city in a sustainable manner. The Sustainable Urban Regeneration Policy has focused on the multiple dimensions of the urban environment of the historical center represented by - the physical dimension, the economic dimension, the social dimension, the cultural dimension and the institutional dimension-, focusing on the physical dimension considering it the most important in the regeneration of historical city centers. Many urban sustainability strategies have focused on regenerating the historical center under the umbrella of sustainable urban regeneration. However, they have not focused on physical aspect as a basis for regenerating the structure of the historical center as a whole. In the 1990s, the Ecopolis strategy has emerged, concentrating on the environmental -physical dimension of the urban structure, that promotes the spatial attraction, thereby improving the quality of life in historic city centers. The objective of the research is to extract the mechanisms and indicators of the Ecopolis strategy in the environmental-physical dimension through three aspects; the urban form, urban efficiency and the flow of elements in the historical center structure, which create a spatial environment that achieves the well-being of the inhabitants. As well as the application of the indicators on an elected environment (Al-Karkh Historical Center).